Investigating Factors and Drivers of Livelihoods Change in Rural Households in Border Regions (Case Study: Minan district, Sarbaz township) - Javad Bazrafshan; Mehrshad Toulabi Nejad; Najmeh Hamli (تحقیقات کاربردی علوم جغرافیایی)
This study explored the factors and drivers of livelihood pattern change in rural households through sustainable livelihoods Approach. The study was considered applicable and used a descriptive-analytic method. To collect the data, questionnaire and interview instruments were utilized. The statistical population was Minan rural households in Sarbaz border province (N=4544). Using Cochran’s sampling technique, 354 households were selected as the participants of the study. One sample t-test, chi-square, and logistic model were used for data analysis. Findings revealed that out of 354 respondents, 72.88 % believed their livelihood pattern had changed and 27.12% supposed no change. 15 out of 45 variables under study were considerably effective and had significant relationships with livelihood variable. Economical (0.400), personal (0.360), and geographical isolation (0.312) factors played major roles in this regard. Moreover, it indicated that out of 354 respondents, 39.8% assumed that they had chosen fuel smuggling, 25.4 % goods trading,  and 22.9 % service works as a reaction to this livelihood change for the living. Thus, it can be argued that integrated rural livelihood and accessible proper foundations for subsistence outside the farms (such as rural industries) can diversify living and prevent both livelihood change and use of illicit and hazardous activities, for instance, fuel and goods smuggling.